LA GUERRE DES CRISTEROS DANS LES RAPPORTS DIPLOMATIQUE ET LA PRESSE. LE MILITANTISME CATHOLIQUE ESPAGNOL-MEXICAIN DES ANNÉES 20 DU XX SIÈCLE (Tzintzun, Revista de Estudios Históricos, 2023)
This article reviews Spanish-Mexican relations during the second half of the 1920s.In addition to reviewing the details of diplomatic relations, it pays special attentionto the links established between Catholic organizations, some intellectuals, thedebates raised in Spanish newspapers, as well as some literary references to theevents of the Cristero War from 1926 to 1929.
Keywords: Guerre des Cristeros; débats; relations diplomatiques hispanomexicaines